LEKSIKON ADAT ISTIADAT PENGOBATAN MASYARAKAT DAYAK JALAI KABUPATEN KETAPANG (KAJIAN ETNOLINGUISTIK) - Wahyu Damayanti (tuahtalino, 2020)
The Dayak Jalai Ketapang people in West Kalimantan are people who live along the Jalai River and its tributaries that empties into the Jalai River. The Dayak Jalai tribe has customs in traditional medicine. The purpose of this study is to describe the lexicon of healing customs of the Dayak Jalai community in Ketapang Regency. This study uses a descriptive method through a qualitative approach. The data in this study were in the form of a lexicon of traditional medicine rituals obtained from literature studies and informants of the Dayak Jalai tribe of Ketapang Regency. The data analysis included classifying the lexicon of traditional medicine rituals. Based on the results of the lexicon analysis of healing customs of the Dayak Jalai community in Ketapang Regency, it can be concluded that there are 4 lexicons of disease causes, 7 ritual lexicons, 9 lexicons of fathering facilities and equipment (special rituals for shamans/balins), 6 balin lexicons, 5 lexicons of facilities and balin equipment.